Committee on Behavioral Science Content of the Accounting Curriculum. (The Accounting Review, 1971)
Abstract This article presents an overview of a report on accounting by the Committee on Behavioral Science Content of the Accounting Curriculum. The charge of this committee was to formulate a statement indicating the general scope of behavioral science material, which should be included in the accounting curriculum, and to suggest methods of incorporating such material into the curriculum. In developing this report, the committee operated within the context of two fundamental assumptions. First, it was assumed that accounting is action oriented; that most accounting reports are intended to provide information for decision-making. Unless accounting reports have the potential to influence decisions and actions, it is difficult to justify the cost of their preparation. For example, the standard of relevance as discussed in "A Statement of Basic Accounting Theory" requires that information must bear upon or be usefully associated with the action it is designed to facilitate or the result it is desired to produce. This requires that either the information or the act of communicating it exert influence or have the potential for exerting influence on the designated actions.